Open Informational Ecosystems: The missing link for sharing resources for education - Michael Kerres; Heinen, Richard (The International Review of Research in Open and Distributed Learning, 2015)
Open educational resources are not available “as such”. Their provision relies on a technological infrastructure of related services that can be described as an informational ecosystem. A closed informational ecosystem keeps educational resources within its boundary. An open informational ecosystem relies on the concurrence of independent stakeholders that jointly provide (meta-) information also beyond its boundaries. Mechanisms of open informational ecosystems are described and how they contribute to the delivery of educational resources and to opening education. The paper describes the case of the German Bildungsserver that aims at establishing a federated network of providers of open and closed educational resources. It points out that the design of (inter-)national informational ecosystems has a major influence on the future of open educational resources in education.